Legal Sanctions Against Companies That Breach The Provisions of Circulation License - Zelfy Aristin (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
Through the decision of the Surabaya District Court Number 728 / Pid.Sus / 2018 / PN.Sb PT. ASAHAN FOOD does not need to stay in prison for 6 (six) months, provided that within the next 1 (one) year the owner of PT. ASAHAN FOOD is of good character. In the case of endangering the public with the decision mentioned above, the verdict in the case of the Surabaya district court has anomalies and has a vague meaning to law no.18 of 2012 concerning food article 91 and article 142 considering that there are still legal loopholes as a criminal act in the case of PT. Asahan Food for deliberately taking steps to ignore it for quite a long time (4 years) since the issuance of the new regulation to administer the permit from BPOM as the agency that has control over the safety of food products. so that this can cause loss and cause of death for the wider community.